2018
DOI: 10.5455/medarh.2018.72.267-271
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Motion Therapy in the Prevention of Lumbar Pain Syndrome Relapse

Abstract: Introduction:Lumbar pain syndrome is one of the most common conditions in clinical practice, more common than 290 other pathological conditions, which affect up to 84% of adults in a certain period of their life. The origin of the lower back pain can be classified as mechanical, neuropathic and secondary due to another illness. Patient education and information, muscle strengthening exercises, maintenance of routine daily physical activity and pain therapy are the basis of acute non-specific pain syndrome ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Most studies evaluated the effect of sex on function ( n = 39), pain ( n = 26), and psychological well‐being ( n = 13; Table 3). No effect of sex was found in 35 studies (Adnan et al., 2017; Alodaibi et al., 2021; Anderson et al., 2011; Beissner et al., 2012; Beneciuk et al., 2013; Berglund et al., 2015; Brennan et al., 2021; Brooks C, Kennedy S, & Marshall PW, 2012; Burns et al., 2018; Cougot et al., 2015; Feitosa et al., 2016; Fisher et al., 2020; Fritz et al., 2019; Fritz et al., 2013; George & Stryker, 2011; Glattacker et al., 2018; Hügli et al., 2015; Jensen et al., 2013; Kaljic et al., 2018; Murphy et al., 2014; Nava‐Bringas et al., 2016; Neyaz et al., 2019; O’Leary et al., 2020; Oliveira et al., 2019; Pak, Miller, & Cheuy, 2021a; Pietsch et al., 2021; Preuper et al., 2011; Rasmussen‐Barr et al., 2012; Schaller et al., 2017; Stapelfeldt et al., 2011; Van Hooff et al., 2014; Van Koppen et al., 2016; Varela & Van Asselt, 2022; Werneke, Hart, George, Deutscher, & Stratford, 2011; Zheng et al., 2018) while 14 studies demonstrated male sex was associated with better outcomes (Bath & Lovo Grona, 2015; de Heer & Warren, 2016; Farin, 2015; Fehrmann et al., 2022; George & Stryker, 2011; Glattacker et al., 2012; Hadizadeh et al., 2020; Lonsdale et al., 2017; Lutz et al., 2020; Meng et al., 2017; Ozcan Kahraman et al., 2018; Park & Lee, 2016; Wilson et al., 2011; Yağcı et al., 2020). Female sex and better outcomes were demonstrated in seven studies (Beneciuk & George, 2021; Görge...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies evaluated the effect of sex on function ( n = 39), pain ( n = 26), and psychological well‐being ( n = 13; Table 3). No effect of sex was found in 35 studies (Adnan et al., 2017; Alodaibi et al., 2021; Anderson et al., 2011; Beissner et al., 2012; Beneciuk et al., 2013; Berglund et al., 2015; Brennan et al., 2021; Brooks C, Kennedy S, & Marshall PW, 2012; Burns et al., 2018; Cougot et al., 2015; Feitosa et al., 2016; Fisher et al., 2020; Fritz et al., 2019; Fritz et al., 2013; George & Stryker, 2011; Glattacker et al., 2018; Hügli et al., 2015; Jensen et al., 2013; Kaljic et al., 2018; Murphy et al., 2014; Nava‐Bringas et al., 2016; Neyaz et al., 2019; O’Leary et al., 2020; Oliveira et al., 2019; Pak, Miller, & Cheuy, 2021a; Pietsch et al., 2021; Preuper et al., 2011; Rasmussen‐Barr et al., 2012; Schaller et al., 2017; Stapelfeldt et al., 2011; Van Hooff et al., 2014; Van Koppen et al., 2016; Varela & Van Asselt, 2022; Werneke, Hart, George, Deutscher, & Stratford, 2011; Zheng et al., 2018) while 14 studies demonstrated male sex was associated with better outcomes (Bath & Lovo Grona, 2015; de Heer & Warren, 2016; Farin, 2015; Fehrmann et al., 2022; George & Stryker, 2011; Glattacker et al., 2012; Hadizadeh et al., 2020; Lonsdale et al., 2017; Lutz et al., 2020; Meng et al., 2017; Ozcan Kahraman et al., 2018; Park & Lee, 2016; Wilson et al., 2011; Yağcı et al., 2020). Female sex and better outcomes were demonstrated in seven studies (Beneciuk & George, 2021; Görge...…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies evaluated the effect of age on function ( n = 35), pain ( n = 23), and psychological well‐being ( n = 11; Table 3). No effect of age was found in 31 studies (Abu et al., 2017; Anderson et al., 2011; Beissner et al., 2012; Beneciuk et al., 2013; Beneciuk & George, 2021; Berglund et al., 2015; Brennan et al., 2021; Burns et al., 2018; Cougot et al., 2015; Feitosa et al., 2016; Fritz et al., 2019, 2011; George & Stryker, 2011; Glattacker et al., 2012, 2018, Görge et al., 2017; Hügli et al., 2015; Kaljic et al., 2018; Murphy et al., 2014; Nava‐Bringas et al., 2016; Neyaz et al., 2019; O’Leary et al., 2020; Oliveira et al., 2019; Pak et al., 2021; Rajamani et al., 2020; Rasmussen‐Barr et al., 2012; Schaller et al., 2017; Stapelfeldt et al., 2011; Van Hooff et al., 2014; Van Koppen et al., 2016; Walston & McLester, 2020), while 16 studies demonstrated that younger age was associated with better outcomes (Adnan et al., 2017; Alodaibi et al., 2021; Bath & Lovo Grona, 2015; de Heer & Warren, 2016; Fritz et al., 2013; Gregg et al., 2014; Harsted et al., 2021; Heidari et al., 2017; Jensen et al., 2013; Lutz et al., 2020; Preuper et al., 2011; Schwind et al., 2013; Verkerk et al., 2015; Werneke, Hart, George, et al., 2011; Wilson et al., 2011; Yağcı et al., 2020). Older age and better outcomes were demonstrated in four studies (Dhondt et al., 2020; Farin, 2015; Fehrmann et al., 2022; George & Stryker, 2011), one study demonstrate...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of adults who suffer from low back pain at some point in their lives is 84%. According to data from the literature, the annual incidence of a first episode of low back pain ranges from 6.3% to 15.6%, the annual incidence of each episode of low back pain ranges from 1.5% to 36%, and recurrence is estimated to range from 24% to 80% on an annual basis (4,5,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…For subacute pain (6-12 weeks), return to daily activities takes up to 3 months. Chronic low back pain (longer than 12 weeks) occurs in 8% of sufferers, and in this case the likelihood of full recovery decreases (8)(9)(10)(11)(12)(13)(14)(15). Pain distribution, dermatomes, reflexes, and myotomes differentiate the clinical picture into local, referential, or radicular pain (radiculitis or radiculopathy), and the distinction between nonspecific/specific and acute/subacute/ chronic pain is useful not only for epidemiological studies but also for choosing appropriate strategies for its diagnosis and treatment (8,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%